SAT0227 Two-Year Retention and Effectiveness of IV Abatacept Monotherapy and Combination in PTS with RA Previously Treated with at Least One Biologic Agent in A Real-Life Setting: Subgroup Analysis from the Action Study. (10th June 2014) - Nüβlein, H.; Alten, R.; Galeazzi, M.; Lorenz, H.-M.; Nurmohamed, M.; Bensen, W.; Burmester, G.-R.; Peter, H.-H.; Pavelka, K.; Chartier, M.; Poncet, C.; Rauch, C.; et al.
Abstract : Background: Although biologic agents should be preferentially used in combination with MTX or other conventional synthetic (cs)DMARDs, 1 monotherapy with a biologic may be considered, especially if there is an intolerance to csDMARDs. Objectives: To assess retention rates and the effectiveness of IV abatacept (ABA) in monotherapy or in combination with csDMARDs (±MTX) over 2 yrs in the real-world ACTION study. Methods: ACTION is a 2-yr, international (Austria, Belgium, Canada, Czech Republic, Denmark, Germany, Greece, Italy, the Netherlands), non-interventional cohort of RA pts who initiated IV ABA between May 2008 and January 2011. ABA retention (and 95% CI) over 24 mths was estimated using the Kaplan–Meier method. Pts who failed ≥1 biologic agent were grouped by treatment pattern at ABA initiation (monotherapy vs combination [± MTX]). The proportion of pts achieving a moderate or good EULAR response was assessed in pts on ABA at 24 mths (as observed). Results: The analysed population comprised 1131 pts; 1009 (89.2%) pts had failed ≥1 biologic agent. ABA was initiated in combination with csDMARDs in 772/1009 (76.5%) pts (MTX in 569/1009 [56.4%] pts) and as monotherapy in 237/1009 (23.5%) pts. Compared with combination, pts in the monotherapy group were older (mean [SD]: 59.1 [12.5] vs 55.3 [12.2] yrs), had longer disease duration (13.9 [10.6] vs 11.2 [8.7] yrs), more comorbidities (77.2 vs 70.6%) and had failed a greater number of anti-TNFs (57.4 vs 47.7% failed ≥2 previous anti-TNFs). In the monotherapy group, previous MTX was discontinued due to intolerance in 68.1% of pts. A total of 161/237 (67.9%) pts were receiving a biologic agent as monotherapy when they switched to ABA. Retention rates at 24 mths were similar for the combination and monotherapy groups (Figure). Similar proportions of pts discontinued ABA for lack of efficacy (34.4 vs 40.0%) or intolerance (9.7 vs 13.7%) in both combination and monotherapy groups, respectively. A good or moderate EULAR response was achieved in 80.6% of pts in the combination group (n=222) and in 78.8% of pts in the monotherapy group (n=61). The safety and tolerability of ABA in the total population are reported elsewhere and were consistent with previously published data. 2 Conclusions: Over 24 mths in a real-life setting, good retention rates were observed with IV abatacept in pts refractory to previous biologic agents. Retention rates were similar when abatacept was initiated in combination with csDMARDs or with concomitant MTX. Retention rates with abatacept monotherapy were similar to combination, although patients on monotherapy had more comorbidities and most were intolerant to MTX, supporting monotherapy use in these patients. References: Smolen J, et al. Ann Rheum Dis 2013, doi: 10.1136/annrheumdis-2013-204573. Nüßlein H, et al. Arthritis Rheum 2012;64(Suppl10):S199. Poster 460. Disclosure of Interest: H. Nüβlein Consultant for: Bristol-Myers Squibb, Abbott, Chugai, UCB, Essex, Wyeth, Pfizer, MSD, Novartis, Roche, Speakers bureau: Bristol-Myers Squibb, Abbott, Chugai, UCB, Essex, Wyeth, Pfizer, MSD, Novartis, Roche, R. Alten Grant/research support: BMS, Speakers bureau: BMS, M. Galeazzi: None declared, H.-M. Lorenz Consultant for: BMS, Speakers bureau: BMS, M. Nurmohamed Grant/research support: The Jan van Breemen Research Institute has received research grants from Roche, Abbott, Pfizer, UCB and BMS, Consultant for: Roche, Schering-Plough, BMS, UCB, Wyeth, Pfizer and MSD, Speakers bureau: Abbott, Roche, Pfizer and BMS, W. Bensen Grant/research support: Abbott, Amgen, BMS, Janssen, Merck, Lilly, Novartis, Pfizer, Proctor and Gamble, Roche, Sanofi-Aventis, Schering, Takeda, UCB, Warner Chilcott, Wyeth, Consultant for: Abbott, Amgen, BMS, Janssen, Merck, Lilly, Novartis, Pfizer, Proctor and Gamble, Roche, Sanofi-Aventis, Schering, Takeda, UCB, Warner Chilcott, Wyeth, Speakers bureau: Abbott, Amgen, BMS, Janssen, Merck, Lilly, Novartis, Pfizer, Proctor and Gamble, Roche, Sanofi-Aventis, Schering, Takeda, UCB, Warner Chilcott, Wyeth, G.-R. Burmester Grant/research support: CClinical trials for BMS, AbbVie, Pfizer, Medimmune, Novartis, Roche, UCB, Lilly, Consultant for: BMS, AbbVie, Pfizer, MSD, Medimmune, Roche, UCB, Speakers bureau: BMS, Abbott, Pfizer, MSD, Roche, UCB, H.-H. Peter: None declared, K. Pavelka Grant/research support: MSD, Pfizer, Amgen, AbbVie, Roche, Consultant for: MSD, Pfizer, Amgen, AbbVie, Roche, M. Chartier Consultant for: BMS, C. Poncet Consultant for: BMS, C. Rauch Employee of: BMS, M. Le Bars Shareholder of: BMS, Employee of: BMS DOI: 10.1136/annrheumdis-2014-eular.1816